Estudio herpetológico en el proyecto de riego Novillopungo retamales en el parque nacional Llanganates. - Puli Quizhpi, Juliette María (2023)
The present research work entitled "Herpetological Study in the Novillopungo - Retamales irrigation project in the Llanganates National Park" highlights the great importance of herpetofauna species in the sectors close to the area of influence designated for the irrigation project, which It is located in the province of Cotopaxi, Latacunga canton in the parishes of Juan Montalvo, Ignacio Flores and Belisario Quevedo; and Salcedo canton Mulliquindil Santa Ana parish. In addition, it is located in the Province of Napo canton Tena, Pano and Talag parishes, since, due to the construction of the three catchments of the irrigation project, the destruction of the habitat has been observed and witnessed of many species, the same ones that have received little attention from studies or proposals for the conservation of amphibians and reptiles. This study has a greater sampling effort to characterize the richness of species in the subalpine rain forest or páramo, Llanganates National Park sector with the objective of assessing the characteristics that are presented through the research process, the abundance and distribution of herpetology. location and information on the conservation status of the species at present. The information gathering was carried out in the months of May, July and August where no major difference in the results was evidenced due to its typical climate of the páramo presented in the four field trips. The evaluation acquired is of a pioneering nature based on qualitative and quantitative methods in the investigation, it was evaluated along a gradient of elevations that goes from 1,200 masl to 4,638 masl. Where the results obtained showed a total record of 3 families, 5 of amphibians and 2 of reptiles, the 22 individuals of the total diversity sampled, all of them, are the result of the four days of effective work in the field in the bioclimatic zone within from the area of influence of the Novillopungo - Retamales irrigation project found within the Llanganates National Park